Pengaruh Motivasi Intrinsik, Komunikasi Persuasif dan Stres Kerja terhadap Komitmen Afektif Studi pada Hotel Yellow Star Ambarrukmo - Annisa Aprillia Kharisma Dewi; Jajuk Herawati; Epsilandri Septyarini (Universitas Batanghari Jambi, 2023)
This study aims to determine (1) the effect of intrinsic motivation on affective commitment, (2) persuasive communication on affective commitment, (3) work stress on affective commitment, and (4) the effect of intrinsic motivation, persuasive communication and work stress together. on Affective Commitment. The research used is the type of quantitative research method. This research was conducted at the Yellow Star Ambarrukmo Hotel. The number of employees is 60 using nonprobability sampling technique. The data collection method uses a questionnaire and is free. This research uses data quality test, classical assumption test including (normality test, heteroscedasticity test and multicollinearity test) multiple linear regression test and hypothesis test. The results of this study indicate that the Intrinsic Motivation Variable has a positive effect on Affective Commitment. Persuasive Communication Variable has a positive effect on Affective Commitment. Job Stress Variable has a negative effect on Affective Commitment. The Variables of Intrinsic Motivation, Persuasive Communication and Job Stress jointly or simultaneously influence the Affective Commitment Variable.